Coeur en santé St-Henri--a heart health promotion programme in a low income, low education neighbourhood in Montreal, Canada: theoretical model and early field experience. Issue 5 (October 1995) - Paradis, G; O'Loughlin, J; Elliott, M; Masson, P; Renaud, L; Sacks-Silver, G; Lampron, G
Abstract : STUDY OBJECTIVE--Coeur en santé St-Henri is a five year, community based, multifactorial, heart health promotion programme in a low income, low education neighbourhood in Montreal, Canada. The objectives of this programme are to improve heart-healthy behaviours among adults of St-Henri. This paper describes the theoretical model underlying programme development as well as our early field experience implementing interventions. DESIGN--The design of the intervention programme is based on a behaviour change model adapted from social learning theory, the reasoned action model, and the precede-proceed model. The Ottawa charter for health promotion provided the framework for the development of specific interventions. Each intervention is submitted to formative, implementation, and impact evaluations using simple and inexpensive methods. PARTICIPANTS--The target population consists of adults living in St-Henri, a neighbourhood of 23, 360 residents. Because of costs constraints, the intervention strategy targets women more specifically. The community is one of the poorest in Canada with 46% of the population living below the poverty line and 20% being very poor. The age-sex adjusted ischaemic heart disease mortality in 1985-87 was 317 per 100, 000 compared with 126 per 100, 000 in an affluent adjacent neighbourhood. RESULTS--Thirty nine distinct interventions have been developed and tested in the community, eight related to tobacco, 10 to diet, seven to physical activity, and 14 which are multifactorial. The interventions include smoking cessation and healthy recipes contests, a menu labelling and healthy food discount programme in restaurants, a point of choice nutrition education campaign, healthy eating and smoking cessation workshops, a walking club, educational material, print and electronic media campaigns, heart health fairs, and community events. CONCLUSION--An integrated heart health promotion programme is feasible in low income urban neighbourhoods but not all interventions are successful. Such a programme requires substantial energy and resources as well as long term commitment from public health departments.